2020
DOI: 10.1111/iwj.13352
|View full text |Cite
|
Sign up to set email alerts
|

Risk for undernutrition and development of pressure injury in hospitalised patients in Brazil: Multicentre prospective cohort study

Abstract: Although pressure injury (PI) is preventable, the number of patients developing this type of injury is still high. In this prospective cohort study, we aimed to assess whether high risk for undernutrition was a risk factor for PI in 1937 patients aged ≥18 at six hospitals in Sao Paulo, Brazil. Patients' risk for undernutrition was assessed using three unique screening tools. Risk for PI was assessed using the Braden Scale. Data were analysed using Poisson regression with robust variance (95% CI, P ≤ .05). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Screening of titles and abstracts was done with 11,517 entries where 123 studies were deemed appropriate for full-text analysis. In the end, 67 studies were included in narrative synthesis, with 32 prospective cohort studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], 26 retrospective record reviews [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Screening of titles and abstracts was done with 11,517 entries where 123 studies were deemed appropriate for full-text analysis. In the end, 67 studies were included in narrative synthesis, with 32 prospective cohort studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], 26 retrospective record reviews [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five studies analysed pressure injury development as a dichotomous outcome [ 18 , 20 , 21 , 23 , 24 , 26 , 27 , 29 , 30 , 32 , 33 , 35 , 36 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 65 , 66 , 68 , 71 , 72 , 74 , 75 , 77 , 79 , 82 , 83 ], 20 studies reported time to the development of pressure injuries [ 19 , 22 , 25 , 28 , 31 , 34 , 37 , 38 , 40 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations